Primary breast lymphoma and HIV/AIDS - Pieter Barnardt; Dylan Narinesingh (AOSIS, 2011)
Primary extranodal lymphoma of the breast is rare and accounts for 0.04 - 0.53% of all malignant tumours, less than 1% of non-Hodgkin's lymphomas (NHLs) and 1.7% of extranodal NHLs.1 Extranodal lymphoma arises from tissue other than lymph nodes and sites that normally contain no lymphoid tissue. This case describes the clinical and treatment dilemma posed by extranodal presentation in an AIDS-NHL patient.